Seeing the World Differently: An Analysis of the Impact of a Sport-Related Study Abroad Program on Global Mindedness - Carrie W. LeCrom; Gregory Greenhalgh; Brendan Dwyer (Journal of Applied Sports Management, 2015)
The purpose of this research was to determine whether there is a difference in the global mindedness of students who have participated in sport-related study abroad opportunities and those who have not. While a vast amount of research exists on the impact of studying abroad in other fields, no research has been published in the sport management field on how study abroad experiences impact students. The current study surveyed alumni of a graduate program at a mid-Atlantic university over a 12-year time frame. The course examined, offered once per year, is a two-week trip to Western Europe that focuses on sport administration in that region of the world. Surveys assessed the global mindedness of alumni, comparing the results of alumni who had attended the trip to those who had not. Results indicate that there were no statistically significant differences in global mindedness between the two groups. When further broken down into the five dimensions of the global mindedness scale, (responsibility, cultural pluralism, efficacy, globalcentrism, and interconnectedness), the only factor in which the difference between the two groups was statistically significant was cultural pluralism, indicating that students who study abroad have higher levels of cultural pluralism than those who do not.
Keywords: global minded; study abroad; cultural differences; sport management; global